Cellulose Fundamental Aspects and Current Trends - Poletto, Matheus; Luiz Ornaghi Junior, Heitor (IntechOpen, 2015)
Cellulose - Fundamental Aspects and Current Trends consists of 10 chapters written by international subject matter experts investigating the characteristics and current applications of this fascinating material. This book will help the reader to develop a deeper understanding about the concepts related to cellulose and the nanocellulose structure, modification, production, dissolution, and application. Biosynthesis mechanisms and medical applications of microbial cellulose are also discussed. This book will serve as the starting point for materials science researchers, engineers, and technologists from diverse backgrounds in physics, chemistry, biology, materials science, and engineering who want to know and better understand the unique characteristics of the most abundant biopolymer on earth.